Credit rationing of small firms by major banks in South Africa - Madziwa, Stephen Rutendo (My University, 2018)
SMEs are key to economic growth, development and fighting unemployment, yet their growth or survival continues to be threatened by their lack of access to credit finance from the major banks in South Africa. This lack of access has been attributed to a lack of creditworthy borrowers. Credit rating, relationships with the banks, the presence of hard information and the availability of collateral or thirdparty guarantees were identified as possible borrower characteristics that might affect the outcome of their loan applications. The study was informed by data collected using a survey-type questionnaire, from which responses were used to ps with the banks, whether they presented hard information or whether they presented collateral or third-party guarantees with their applications and the outcome of the loan applications. Having relationships with the banks or presenting hard information were found to be insignificant factors in predicting the applications. A good credit rating, defined as having a credit scores above a threshold value, or the presence of collateral or third-party guarantees or both, give the borrower a good chance of loan application success. Small businesses in South Africa need to maintain a good credit rating or be able to present collateral or third-party guarantees if their loan applications at the major banks are to be successful.
MBA
Keywords: Small business -- South Africa -- Finance. Bank loans -- South Africa.